Hubungan U-Shaped antara Kinerja ESG dan Profitabilitas Perusahaan Sektor Manufaktur di Indonesia - Kurniawan Bagas; Hermanto Siregar; Tony Irawan; Tanty Novianti (Jurnal Akuntansi dan Bisnis, 2025)
This study examines the nonlinear effect of environmental, social, and governance (ESG) performance on firms’ return on assets in Indonesia. The study uses panel data on 12 manufacturing firms listed on the Indonesia Stock Exchange during 2017–2023, sourced from Refinitiv Eikon. The estimation is conducted using a fixed-effects panel regression with robust standard errors. ESG is included as the natural logarithm of the ESG score and its squared term to test a U-shaped pattern. The results show that the coefficient on log ESG is negative and statistically significant, while the coefficient on squared log ESG is positive and statistically significant. These findings indicate that ESG improvement at lower levels tends to reduce profitability, but at higher levels it tends to increase return on assets. In addition, leverage and the COVID-19 period reduce return on assets, whereas operating liquidity increases return on assets.